SCHOOL PERFORMANCE EVALUATION SYSTEM FOR THE MUNICIPALITY OF MARILIA (SAREM): USAGE OF RESULTS IN EDUCATIONAL POLICY - Padua Sabia, Claudia Pereira de [UNESP] (Unesp-faculdade Ciencias & Letras, 2020)
Study reports that at the state level, of the 27 Brazilian states, 20 already have their own evaluation systems and 1573 municipalities also have their own evaluation systems, most of which were created in 2005. In 2004, the municipality of Marilia created its own evaluation system. The aim of this study is to identify the possible uses of SAREM results in the formulation and implementation of educational policy in the municipality. The research was developed in a qualitative approach and the methodology used bibliographic and documentary research. As a result, we present that SAREM have been guiding the management developed in schools, influencing the elaboration of the pedagogical project, directing the work of the teacher and spreading a restricted notion of quality to the public school, as it had practically considered the performance of students in large scale assessments as a quality indicator of the work developed by the school.
Keywords: Educational evaluation; Large scale assessment; SAREM; Educational management; Continuing education